Efektivitas Metode Pembelajaran Memorization Dalam Meningkatan Pemahaman Matematika Peserta Didik Di Kelas VII PMDS Putri Palopo - Hasni Hasni (Fakultas Tarbiyah dan Ilmu Keguruan, 2020)
Abstract[English]:The main problem in this study is how effective the memorization learning method is in improving the mathematics understanding of students in class VII PMDS Putri Palopo. This research is experimental, has the character of